Characteristics of Sedimentary Organic Matter and Phosphorus in Minor Rivers Discharging into Zhejiang Coast, China - Pei Sun Loh (Geosciences, 2020)
In this study, the spatial distribution of lignin-derived phenols, bulk elemental composition and different phosphorus (P) species in surface sediments along six rivers discharging into Zhejiang coast, Southeast China, were investigated to improve the understanding of the carbon and P dynamics in these small river systems. The Shuang, Jiao, Ximen, Feiyun and Ao Rivers have total organic carbon (TOC) ranging from 0.29% to 2.77% and Λ (total lignin in mg/100 mg TOC) ranging from 0.24 to 4.24; Qiantang River has the lowest Λ (0.08–0.19) but the highest TOC (1.05%–6.46%). Jiao, Ximen, Feiyun and Ao Rivers have mean the total P (TP) and bioavailable P (BAP) of 34 to 124 mg/kg and 29 to 89 mg P/kg, and mean OC/OP molar ratio of 397–917. Qiantang River has the lowest mean TP and BAP of 13 mg P/kg and 7 mg P/kg, and highest OC/OP of 18,753; whereas Shuang River has the highest mean TP and BAP of 645 mg P/kg and 559 mg P/kg, and lowest mean OC/OP of 90. The lowest Λ, TP and BAP, but highest OC/OP, in the Qiantang River could be due to tidal bore causing rapid cycling of carbon and P. Trends of slight decrease in abundance of OC, Λ, TP and BAP, but increasing ratios of vanillic acid to vanillin [(Ad/Al)v], syringic acid to syringaldehyde [(Ad/Al)s] and OC/OP farther downstream of the rivers indicate a continuous decomposition of organic matter during transport along the rivers.